Cultura, movimento e hip-hop: produções alternativas e resistência cultural em Feira de Santana - Silva, Renata Carvalho da (2015)
This research aims reflecting about the artistic hip-hop productions and performances groups in Feira de Santana. Hip-hop is understood today, as the articulation of four teams / artistic elements that are part of the creative essence of the movement, they are: the disk jockey, the master of ceremonies, the break dancer and the graffiti artist, we can still consider a fifth team that is one relating to political activism. In the context of the city, we see the increasing presence of two of these elements, these are graffiti and rap’s manifestations. Over the past decade the hip-hop has been working in the cultural scene of Feira de Santana with the presence of two participative groups, the H2F association and the crew of graffiti artists NDF. These, in turn, have changed the relationship of subjects in the city, building artistic interventions and creating new spaces for dialogue and articulations. We find in Feirense scene, the emergence of independent cultural projects built by the hip-hop groups, which are organized to keep up culturally "alive" in the artistic context of the city. These groups demonstrate a preocupation to provide training (discussion) between their participants and lay hold of the effort and collective support for the dissemination of productions of rap groups, graffiti and break, and for the financing and organization of events, such as making shows , task forces, lectures and speeches. Considering hip-hop’s importance as a movement able to modify the models of creative participation and provide visibility peripheral culture, we try to understand, how was the hip-hop’s emergence and diffusion in the city of Feira de Santana, analyzing how they are organized groups in the construction of production and how young people fall into the hip-hop culture, as well as what the meanings are attributed to artistic practices within the social dimension Feira de Santana of hip-hop. It was used the qualitative research methodology, collections and observations being employed, using social networks and specialized websites as source of information and participants’ identification. As collection instruments semi-structured interviews were conducted, photographs and notes in notebook. Speeches and photographs’ analysis is based on the ethnographic method.